Health of Tribal Population in India: A Glimpse of the Current Scenario - Angel Ivy Linda; Debkumar Pal; Nisha Murmu; Manish Taywade (Current Medical Issues, 2024)
Article 366(25) of the Indian constitution refers to indigenous people as “scheduled tribes,” which constitute 8.6% of the country’s population. For decades, the health of the tribal people had remained neglected and incorporated in rural health care because of incorrect assumptions of their similar health needs to that of the rural population. An expert committee coordinating with the Ministry of Health and Family Welfare and the Ministry of Tribal Affairs provided a detailed report on the current scenario and recommendations related to tribal health in India. They considered the health-care needs of the tribal population, highlighted their specific health problems, and gave a roadmap of best approaches. The tribal population has a unique and higher burden of health problems than the mainstream population, influenced by their health-seeking behavior, lack of awareness and education, sociocultural and magico-religious beliefs, customs, and practices. The current health-care system incorporates their health needs with approaches such as differing population norms in tribal areas, nonmonetary incentives to staff, mobile medical units, identification of high-priority districts, and the emergence of the “Swasthya” portal. However, tribal health is transitioning as with the rest of the population. Moreover, the present health-care services are unable to address this. Legal recognition of indigenous peoples’ rights to self-determination, their land, natural resources, and their knowledge is a need of the hour.